DEVELOPMENT OF FLIP PDF E-MODULE BASED ON A SCIENTIFIC APPROACH TO IMPROVE PROBLEM SOLVING AND SPATIAL ABILITY FOR STUDENTS MIN 2 SERDANG BEDAGAI - Ismail Ismail (SENSEI RESEARCH CENTER, 2022)
This study aims to: 1) Analyze the validity of the e-module flip pdf based on a scientific approach in improving the spatial ability of students at MIN 2 Serdang Bedagai. 2) Finding a pdf flip e-module based on a scientific approach that is practical in improving the spatial ability of the students of MIN 2 Serdang Bedagai. 3) Finding a flip pdf e-module based on an effective approach in improving the spatial ability of students at MIN 2 Serdang Bedagai. This research is a development research. The development model used in this study is the 4-D Thiagarajan model. The results showed that: 1) E-module flip pdf based on scientific approach that was developed meets the criteria of validity, practicality and effectiveness; 2) The increase in spatial ability using the e-module flip pdf based on a scientific approach increased in terms of the Ngain trial I by 0.30 with low criteria and in the second trial by 0.37 with moderate criteria.